External Economies and the Falling Supply Curve - Adams, Robert W.; Wheeler, John T. (Review of Economic Studies, 1952)
Robert W. Adams, John T. Wheeler; External Economies and the Falling Supply Curve1, The Review of Economic Studies, Volume 20, Issue 1, 1 January 1952, Pag